(untitled) (Archives of Criminology, 1982)
The new Polish penal legislation of 1969 introduced special rules of criminal liability of young adult offenders’ aged 17-20. In 1972 criminological research was undertaken in order to characterize this group of offenders, i.e., its most numerous category - those found guilty of offences against property. The research ended in 1975. In 1980 a follow-up of convictions of the persons, under observation was carried out. The object of the study of young adults found guilty of offences against property was to analyse the psycho-social factors connected with their social maladjustment and demoralization, particularly their family and school environment, personality, extent of drinking and offending. It was also the object of the study to compare two groups of young adult towards whom different measures had been adjudicated. As the most typical offences of young adults are those against property, a group of young adults convicted for this very type of offences was included in the study. There were 100 persons under examination who had been sentenced to immediate imprisonment. This group consisted of all prisoners of two Warsaw prisons in the years 1973-75 (group A). The group of young adults (group B) consisted of 100 persons conviced in 1973 for offences against property and sentenced to fine, limitation of freedom, imprisonment with suspension of execution, or educational-corrective measures. The two groups of convicted persons that were selected for the study, different as regards the adjudicated and executed measures, were compared in many respects in order to ascertain the distinctions between them as regards the degree of intensity of the process of social maladjustment which had been related to the application of various penal measures. Empirical research consisted in gathering detailed information on the persons under scrutiny concerning their previous convictions, their school career and the course of work. Also interviews were carried out with them and separately with their mothers, by means of a detailed questionnaire. Three psychological tests were also employed towards each person, that is Raven’s intelligence test, Eysenck’s questionnaire to measure extroversion and neurotism and Buss-Durkee inventory to measure aggression. 3.1. Offences against property constituted the criterion for selection to the study. The most numerous group were convictions for larceny qualified as “stealing in a particularly audacious manner or by a breaking and entering” (Art. 208 of the Penal Code), though the “audacious theft” was extremely rare as compared with the second choice. 64% of the persons of group A had been convicted for offences described in this article, the percentage as regards group B being 35%. Many persons also committed thefts of social property, while the receiving of stolen goods was the least frequent. Generally, the persons of group A had been active for a longer time than those of group B, and their offences were more frequently qualified as continuous. It should also be emphasized that the mean value of the objects stolen by the persons of group B was considerably lower than it was the case with the young adults of group A. It also happened (16% of cases) that the act of the young adults of group B ended as a mere attempt at committing an offence. To sum up, the offences against property committed by the persons, sentenced to immediate imprisonment were more serious than those committed by the young adults towards whom other measures had been adjudicated. 3.2. 69% of the persons of group A had cases in juvenile courts, while as many as 84% admitted having committed offences, mostly thefts, at that age. On the other hand, 44% of the persons of group B had committed offences for which they were brought to court as juveniles. The difference between both groups is significant (p < 0.00l). The origins of delinquency dating back from before the age of 13 were found in as many as 23 persons of group A and 10 persons of group B. The earlier they started to commit offences and had their first case in juvenile court, the more numerous were their subsequent convictions in that period. The mean number of convictions in juvenile court was 2,2 in group A and 1,6 in group B. The structure of delinquency of the persons under examination is hardly differentiated: they committed first of all offences against property (85.7%), mostly larceny. The juvenile court, had employed such measures as admonition and charge of parents in the case of persons of group B considerably more frequently than towards those of group A (25% and 8.7% respectively). On the other hand, the persons of group A had been much more frequently sent to children’s homes and to corrective schools (44.9%) than those of group B (25%). 3.3. In the period discussed below all the persons were young adults, with the mean age similar in both groups: 19 in group A and 18.9 in group B. The mean number of convictions of the persons of groups A from the age of 17 was 1.7, and in group B 1.2. Each member of group A was responsible for 3.3. offences, while in group B the mean number of offences was 2.2. It should not be forgotten that many persons, particularly those of group A, were repeatedly imprisoned in the discussed period. A considerable majority of the persons of both groups who had committed more than one offence, were convicted for offences against property only. The data quoted above illustrate the whole of delinquency of the persons under examination and recidivism among them. Taking into account both the period of minority and the later period from 17 years of age on, there were as many as 4 per every five persons of group A who had already been convicted before, and in group B nearly every second person had had a conviction previously (the difference is significant, p < 0.01). These data confirm the conclusion as to the more advanced process of demoralization of the young adults of group A as compared with group B. 49% of the persons guilty of offences against property of group A came from unbroken homes; the respective percentage in group B was 71% (difference significant, p < 0.001). Broken homes resulted mostly from the death of one parent (23% of cases in group A and 15% in group B), or from divorce (28% of cases in group A, 14% in group B). A majority of the persons came from workmen’s families (90.5% in group A, 70.7% in group B). The level of professional qualifications and education of parents of the persons examined is significantly lower (p < 0.01) in group A as compared with group B. Approximately 60% of families of the persons of group A and 67% of group B had been living in poor financial conditions, which was connected, among others, with excessive drinking of the fathers. 56.3% of fathers of the persons of group A had regularly been drinking excessively, that is drinking vodka at least twice a week. This percentage was only 26.3% in group B, it was lowered, however, as the examination of young adults of young adults of group B was carried on at home, often with the fathers themselves present. 37% of fathers in group A and 19% of those in group B had been taken to a detoxication centre, including 21% and 14% respectively taken at least three times. As in other criminological studies, in the present one young adults have not been found to live in criminal family environment. It was extremely rare that the fathers of the persons examined had criminal records. To sum up, certain negative phenomena were more frequent in the families of young adults of group A (for instance, broken home, excessive drinking of fathers). However, the cumulation of a number of negative factors could have influenced in a particulary unfarourable way the process of socialization of the persons under examination. 5.1. There were 37% of the persons of group A and 23% of those (p< 0.001) of group B with elementary education, and 18% and 5% respectively with incomplete elementary education. The difference is significant (p < 0.001). School retardation which appears more often among delinquents than among non-delinquents is connected with a lower level of education of young adults. Among the young adults of group A as few as 17% revealed no retardation, the percentage as regards group B being 46.5%. The difference is significant (p < 0.001). The retardation of the persons of group B usually amounts to one year only, while it is often 3 years or more among the persons of group A. School problems are also connected with truancy (group A - 78%, group B – 66% of the examined persons), which begins in the very first grades of elementary school. Early and regular truancy of the persons of group A was one of the symptoms of their maladjustment. Truancy is conducive to running away from home. The persons under scrutiny, particularly those of group A, had been running away from home considerably often and for longer periods. 2. Among those who were employed, every second person in group A and every fifth person in group B worked casually only. They usually took jobs requiring low professional qualifications, as only few of them had any professional training (group A-38%, group B-62%). 6.1. Raven’s test was employed to estimate the level of intelligence of the persons examined. 53.6% of young adults of group A and 31.7% of group B scored low and very low (up to 25 centile). 10.3% of group A and 29.3% of group B scored high and very high (centile 75 and more). The mean score was 35.4 in group A standard deviation: 9.87, and 41.1 in group B (standard deviation 10.09). The difference between both groups is significant (p < 0.01). Low scares on the Raven’s scale were often found among those persons whose level of education had been low, which was accompanied by a considerable school retardation. 2. To measure the level of extroversion and neurotism, Eysenck’s MPI scale was employed. The level of extroversion and neurotism among the young adult perpetrators of offences against property was not found to be higher than that of the average youth. 6.3. The level of aggressiveness was examined by means of the Buss-Durkee questionnaire. None of its scales differentiated significantly the persons of both groups. The mean total score was 61.7 (standard deviation 21.4) in group A and 61.06 (standard deviation 23.6) in group B. The data given below concern the persons of group A only, as the information obtained from those of group B as to the volume and frequency of drinking among them do not seem reliable. The analysis of statements of the subjects reveals that the percentage of teetotallers diminishes with age. The persons examined have been drinking large amounts of alcohol from their earliest years. 36% of them stated that they had drunk such quantities of various spirits at the age of 15, which converted to 40 proof vodka would amount to 2.5 litres a month. From the age of 17 on, 60% of the persons drank over 2.5 litres of 40 proof alcohol a month. They drank vodka as well as wine and beer, which leads relatively quickly to the “treshold of intoxication”. Mean yearly consumption of alcohol per 1 examined person was 34.2 litres at the age of 15, and increased sed from year to year to reach 113.7 litres yearly at the age of 19, which means that approximately 9.5 litres of 40 proof vodka were consumed monthly; this quantity goes far beyond the mean level of drinking by men at this age. 3/4 of the subjects can be recognized as excessive drinkers. A significant correlation was found between the excessive drinking among the persons under scrutiny and their early delinquency and recidivism. The highest percentage (40%) of the persons who did not drink excessively was found among those convicter once only, while the lowest (14.8%) was found among those who had 5 or more convictions. The analysis of the young adults’ information as to their , peer groups revealed that also their closest friends had been drinking excessively and often intoxicated. In February 1980, further convictions of the persons examined, then aged 25 on the average, were checked up again. As revealed by the analysis, the persons of group A (60%) still continued to commit offences and indeed many of them become multiple recidivists. The difference between the persons of groups A and B is significant (p < 0.001). 40% of the persons of group A and 67% of those of group B have not been convicted within the period of the follow-up. The majority of the persons under observation continued to commit offences against property. The courts have mainly adjudged the penalty of immediate imprisonment (group A - 92.3%, group B - 78.2%). Among those sentenced to immediate imprisonment there were in group A 57.1% sentenced to 2 years or less of imprisonment, and in group B - 93%. There was significant correlation (p < 0.01)between the convictions in juvenile courts and further convictions in the period of the follow-up. As the data reveal, group B towards which the sanctions other than immediate imprisonment were adjudicated, differed from the imprisoned group A as to the smaller extent and intensity of their offending - also during the follow-up - and their lower degree of progress in the process of social maladjustment. However, there were quite many persons in group B as well (though less than in group A), who had been convicted as juveniles; they had yet no convictions during the follow-up in a much highter percentage of cases than the subjects of group. A who had been convicted by the juvenile court previously. On the basis of the above information, criminal policy can be discussed as regards young adults found guilty of offences against property. One should not postulate a total abandonment of the penalty of immediate imprisonment, and yet, as shown by the above data, its adjudgement should be considerably limited. The limitation in question should concern first of all young adults convicted for the first time and socially demoralized to a small degree. Within the years 1970 -76 imprisonment was the measure most frequently adjudicated towards young adults. In the years 1970 - 1974 the percentage of young adults sentenced to immediate imprisonment increased regularly. It is only since 1975 that a favourable phenomenon of regular decrease of the percentage of adjudicated penalties of immediate imprisonment can be noticed, with simultaneous increase of the percentage of measures which are not connected with deprivation of liberty. As it seems, the application of immediate imprisonment towards young adults should undergo further limitations. When postulating the re-orientation of the criminal policy of the courts towards a maximum realization of the instructions of Art. 51of the Penal Code, one should also demand changes in the stage of execution of penalty. As indicated , by many studies of readaptive effectiveness of corrective schools and prisons, their influence is minimal and sometimes their resocializing activities are destructive for the convicted persons. Imprisonment causes a state of deprivation of essential physical and mental needs, destroys the ties of those convicted with their family, gives rise to socially negative patterns of prisoners’ subculture. In the present study also the offenders of group A were described, the considerable part of whom had been changing various types of institutions and prisons, first as juveniles, then as young adults, and the effects of these imprisonments were negative as measured by further convictions within the period of the follow-up. The information presented in this study concerning the family background of the persons of group A (particularly the alcoholism or excessive drinking of the fathers, which is frequent in these families), and information concerning the early and large social maladjustment of these persons, indicate a need to consider the problem of young adult perpetrators of offences against property not only in relation to the measures that should be adjudged and their execution. It is also of almost importance to consider the prevention of social maladjustment of this category of youth.